Interdisciplinary Research of Magnetic Fields and Life Sciences - An, Liaoyuan; Chen, Guangdi; Chen, Peiyao; Chen, Shizhen; Chen, Xin; Chen, Zhong; Deng, He; Dong, Dandan; Fang, Zhicai; Gu, Ning; Guo, Qianni; Guo, Zhichuan; et al. (Current Natural Sciences, 2021)
Magnetic field is a ubiquitous physical field. Humans have long been aware that certain birds can use the Earth's magnetic field to navigate. Indeed, such phenomenon inspired people to explore the biological effects of magnetic field and the underlying mechanism. The man-made ultra-high or ultra-weak magnetic fields provide excellent experimental conditions for material sciences and life sciences. Since the beginning of the 1990s, magnetic resonance imaging (MRI) has been widely introduced as a stand-alone diagnostic technique in hospitals. As the image quality of MRI is positively correlated with the strength of the magnetic field, MRI instrument equipped with ever stronger magnet has been built, from 1.5 to 3 Tesla and higher. There is an urgent need to understand the safety limit of the maximum magnetic field strength on human health. This book mainly focuses on the progresses of inter-disciplinary researches of high magnetic fields and life sciences by researchers from mainland China. The topics covered can be roughly divided into two major categories. One is to study the effects of high magnetic fields on biological samples, such as cell, humans and animals. The other is to utilize techniques that based on high magnetic field to study biological questions, such as using NMR (Nuclear Magnetic Resonance) and MRI (Magnetic Resonance Imaging) in structural biology and medical imaging. The researches about the biological effects of high magnetic fields are very interesting and inspiring, but still at a very initial stage. More studies are needed to promote the scientific development of this field, and their potential applications in medicine